Effect of in situ sediment remediation combining oyster shells and bottom microporous aeration on nitrogen removal and microbiota. (18th November 2018) - Wang, Miao; Yi, Mengmeng; Lu, Maixin; Zhu, Xi; Chen, Guoliang; Gao, Fengying; Liu, Zhigang; Cao, Jianmeng; Zhang, Defeng
Abstract: The present intensive aquaculture results in an excessive accumulation of nutrient and organic residues in sediment. Then, pollutants accumulated in sediment would strongly affect water quality and increase the occurrence of pathogenic microorganisms. Thus, remediation of sediment is needed for removing excess nutrient and preventing aquatic animal diseases. In the present research, sediment in cement tanks was remediated with a combined method: crushed oyster shells (OS) and bottom microporous aeration (MA) treatment. The experiment included the control group (CK), treatment 1 (bottom MA), treatment 2 (crushed OS), and treatment 3 (bottom MA and crushed OS, MA+OS). The experimental results showed that from the second week after the experiment began, the organic matter (OM) content in the sediment from MA+OS was lower than that of the CK. From the eighth week, the total nitrogen (TN) and ammonia nitrogen (NH4 ‐N) levels in the sediment from MA+OS were lower than those of CK, and the remediation experiments on sediment had little effect on the water quality in the experimental groups. Functional bacteria in the water column, including the families Erythrobacteraceae and Microbacteriaceae and the genera Phenylobacterium and Beggiatoa, were elevated in MA+OS. Thus, crushed OS and bottom aeration could promote nitrification in water, reducing the levels of OM, (NH4 ‐N), and TN in sediment, through affecting the microbiota in the water column and promoting nutrient circulation, and could improve the overall benthic environment. The method has been demonstrated to be easy and effective for nitrogen removal from sediment.